Prevalencia de toxocara cati en Felinos domésticos (felis catus) en el sector la Venecia II del Distrito Metropolitano de Quito - Gaguancela Padilla, Miguel Bladimir (2021)
Parasitic zoonosis constitutes a very important public health problem in all regions of our country; When companion animals present these types of problems, it can be very common for parasites to infect the owners and depending on the parasite and their quantity, it can cause some health difficulties. The present investigation helps us to determine the prevalence of Toxocara cati in domestic felines in the Venice II sector of the Metropolitan District of Quito through stool tests with the Float Concentration method and the Sheater Sucrose technique does not disclose the percentage of prevalence that Toxocara cati has in the La Venecia II sector, for which 100 samples of cats were used and 15 positive samples were obtained, with this we established a prevalence percentage, which is 15%, in addition The variables of sex and age were established to know in which stages the parasite is most present with a result of 4% in cats under one year, 9% from 1 to 3 years and 2% older than 3 years, with age a percentage of 9% in males and 6% in females. Stool tests are a fundamental part of determining any type of parasite present in the cat samples. Through proper handling of the sucrose technique, the parasite raised in the investigation was correctly identified and with the data obtained a percentage of prevalence over the number of samples used as a sample.